Angling in Cultural and Provisioning Ecosystem Services - Karpiński, Emil Andrzej (Polish Journal of Natural Sciences, 2023)
Recreational fishing is one of the most common recreational activities in the aquatic environment and a very complex social-ecological system (SES). It provides real benefits to anglers and as such, is considered an ecosystem service (ES). This article seeks to identify the scale and nature of cultural and provisioning ES in angling concerning socio-economic and engagement indicators. It also focuses on affiliation and preferred company of other anglers and preference for fishing in different waterbodies. Cultural service anglers were most numerous (68.5%) in this context and were clearer in their environmental and social preferences and characteristics. Anglers expecting to provision are harder to classify, making their behavior in the environment less certain. Association in organizations/clubs proves to be a key social factor that can influence anglers in the context of final ES choice. Despite uneven distribution, the lakes are the most frequently preferred by anglers.